2004
DOI: 10.1021/op034137w
|View full text |Cite
|
Sign up to set email alerts
|

Solvent and Temperature Effects in the Free Radical Aerobic Oxidation of Alkyl and Acyl Aromatics Catalysed by Transition Metal Salts and N-Hydroxyphthalimide:  New Processes for the Synthesis of p-Hydroxybenzoic Acid, Diphenols, and Dienes for Liquid Crystals and Cross-Linked Polymers

Abstract: The aerobic oxidation of 4,4′-diisopropyldiphenyl and 2,6diisopropylnaphthalene, catalysed by N-hydroxyphthalimide and Co(II) salts, leads to the corresponding tertiary benzyl alcohols with high conversion and selectivity under mild conditions (temperature 30-60 °C and atmospheric pressure). Solvent and temperature effects, as resulting from the pioneering work of C. Walling, and more recently from the conclusive resolution of K. U. Ingold and co-workers on a quantitative kinetic basis, strongly affect the sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
34
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 17 publications
3
34
1
Order By: Relevance
“…The hydroperoxide in cumene oxidation reaction catalyzed by NHPI/CH 3 CHO system under moderate conditions at 25°C was obtained with a yield of approximately 50 % [13]. In contrast, the products of the oxidation of isopropylaromatic hydrocarbon catalyzed by NHPI and variable-valence metal salt systems primarily contained the corresponding alcohols and ketones [14][15][16][17]. The combination of NHPI and Co(OAc) 2 in PEG-1000 based dication ionic liquid led even to formation of benzoic acid in the cumene oxidation reaction [18].…”
Section: Introductionmentioning
confidence: 98%
“…The hydroperoxide in cumene oxidation reaction catalyzed by NHPI/CH 3 CHO system under moderate conditions at 25°C was obtained with a yield of approximately 50 % [13]. In contrast, the products of the oxidation of isopropylaromatic hydrocarbon catalyzed by NHPI and variable-valence metal salt systems primarily contained the corresponding alcohols and ketones [14][15][16][17]. The combination of NHPI and Co(OAc) 2 in PEG-1000 based dication ionic liquid led even to formation of benzoic acid in the cumene oxidation reaction [18].…”
Section: Introductionmentioning
confidence: 98%
“…[5,8] A few years ago we reported that an NHPI/Co(II) catalytic system could efficiently promote the selective aerobic oxidation of diisopropyl aromatic compounds to the corresponding tertiary alcohols in high yields. [9] Very recently Orliń ska has reported a detailed investigation of the catalytic system consisting of NHPI in combination with various Cu(II), Co(II) and Mn(II) salts for the oxidation of cumene with oxygen. [10] However, as mentioned before, in order to directly obtain the desired hydroperoxides, the presence of transition metal salts is generally detrimental.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible to tune the catalytic efficiency of NHPIs in the oxidation by introducing electron-withdrawing substituents in NHPI. Since aerobic cumene oxidation is the main stage of industrial process of phenol and acetone production, the possibility to use NHPI to enhance the selectivity and conversion was studied earlier [5,6]. The author [7] studied the influence of different catalytic systems (NHPI/metal salt) on the product distribution in the aerobic cumene oxidation without NHPI structure variation.…”
Section: Introductionmentioning
confidence: 99%